The relationship between corporate social responsibility and corporate financial performance: Evidence from a developing country - Hossain, M.; Chowdhury, M.; Evans, Robert; Lema, A. (Virtus interpress, 2015)
We investigate the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) in a developing country context using annual report data from a sample of 131 firms over a 5 year period (2008-2012). Legitimacy theory and stakeholder theory underpin the study. We find a positive and significant relationship between CSR and CFP when using accounting measures of return on assets and equity, but an insignificant relationship when using the market based Tobin’s Q. The moderating effect of organisational governance on measures of workplace and environmental reporting is found to be important in a less developed economy.